2000
DOI: 10.1063/1.1306243
|View full text |Cite
|
Sign up to set email alerts
|

Diffractive acoustic elements for laser ultrasonics

Abstract: Laser ultrasonics is an effective means of generating surface acoustic waves ͑SAWs͒. We have shown in previous publications how computer-generated holograms ͑CGHs͒ can be used to project optical distributions onto the sample surface. These can be used to control both the frequency content and the spatial distribution of the resulting ultrasound field. In this paper the concept is extended further to produce distributions which themselves act as diffractive acoustic elements ͑DAEs͒ for SAWs. It is demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Laser induced ultrasonic arrays have been proposed as early as 1968 [10] by spatial modification of the laser beam. Using this method, previous work from the authors of the present article, has shown successful control of focusing and steering of surface acoustic waves and longitudinal waves [11][12][13]. Another option is to use temporal modification of the laser and two methods of phased arrays using laser ultrasonics have been proposed in the past: using a single laser source with multiple optical delays and using multiple laser sources.…”
Section: Introductionmentioning
confidence: 89%
“…Laser induced ultrasonic arrays have been proposed as early as 1968 [10] by spatial modification of the laser beam. Using this method, previous work from the authors of the present article, has shown successful control of focusing and steering of surface acoustic waves and longitudinal waves [11][12][13]. Another option is to use temporal modification of the laser and two methods of phased arrays using laser ultrasonics have been proposed in the past: using a single laser source with multiple optical delays and using multiple laser sources.…”
Section: Introductionmentioning
confidence: 89%
“…The experimental setup to generate and detect shaped SAW distributions has been described elsewhere [3,4], thus we concentrate on the salient features and the differences. A modelocked Q-switched Nd-YAG laser emitting 1064 nm radiation is incident on the spatial light modulator (Displaytech model 256A), the light distribution reflected from the SLM is imaged onto the sample surface.…”
Section: Experimentmentioning
confidence: 99%
“…The use of moving gratings [1] is an example of (i), whereas the use of an axicom to focus the generating light into a ring on the sample is an early example of generating focused SAWs [2]. The present authors have been active in the use of computer generated holograms (CGHs) to produce arbitrary light distributions, which can both spread the generating power and focus the resulting SAW distribution [3]. This is a very efficient way to generate large SAW amplitudes without sample damage.…”
mentioning
confidence: 99%
“…A variety of optical techniques have been used to image electrically excited [1][2][3][4][5][6][7] or laser-excited [8][9][10][11] surface acoustic waves (SAWs) on solids and microstructures. When point-focused laser pulses are used for the SAW generation, the resulting omnidirectional twodimensional wave field can be mapped in the time domain and then Fourier-analyzed to obtain the in-plane acoustic dispersion relation [9,[12][13][14].…”
Section: Introductionmentioning
confidence: 99%